Smart green supply chain management: a configurational approach to enhance green performance through digital transformation - Lerman, Laura; Benitez, Guilherme Brittes; Müller, Julian; De Sousa, Paulo Renato; Frank, Alejandro German (Supply Chain Management-An International Journal, 2022)
Purpose: While it is known that digital transformation facilitates data flow in supply chains, its importance on green supply chain management (GSCM) has not been investigated concisely. This paper aims to expand the theory of digital transformation in GSCM by investigating the interconnections between these concepts and providing an integrative view of a smart green supply chain management (Smart GSCM). Design/methodology/approach: This adopts a configurational perspective on digital transformation and supply chain management (SCM) to investigate the different dimensions of Smart GSCM and their contribution to green performance. Therefore, this paper analyzes data from 473 manufacturing companies using regression techniques. Findings: The results show how smart supply chain contributes to green performance through managing green relationships (external GSCM activities) and establishing green operations (internal GSCM activities). Furthermore, this paper finds partial mediating effects for external and internal GSCM activities on green performance. These findings show that smart supply chain (i.e. digital transformation strategy and front-end technologies, supported by several back-end technologies) is directly associated with higher levels of GSCM. It is specifically associated with one of the internal dimensions of green operations, namely, green purchasing activities. Hence, the findings suggest that digital transformation alone is insufficient to achieve green performance, needing a GSCM configuration to mediate this effect. Practical implications: This study calls attention to how managers should integrate these at least three different perspectives of SCM: digital transformation, external relationships and internal operations to increase green performance. Originality/value: As the main contribution, this study provides a configurational and holistic understanding of the different dimensions and mechanisms in Smart GSCM.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Digital transformation; Green operations; Green supply chain management; Smart supply chain; Sustainability